The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.envsci.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Managing forest ecosystem services for hydropower production

Abstract: published by Elsevier. It is posted here by agreement between them. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…The recharge in the basin increased 6% in the scenario with the lowest percentage of reforestation, reaching 20% in the scenario of a higher percentage of restoration (30%). These results reflect a regularization of the base flow, more visible in sub-basins (Vogl et al, 2016). The components of the water balance are affected by the reforestation of cultivated areas, mainly the groundwater recharge (Woldesenbet et al, 2017), with the increasing soil water infiltration (Yu et al, 2015), as well as a significant reduction of runoff (Li et al, 2012).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The recharge in the basin increased 6% in the scenario with the lowest percentage of reforestation, reaching 20% in the scenario of a higher percentage of restoration (30%). These results reflect a regularization of the base flow, more visible in sub-basins (Vogl et al, 2016). The components of the water balance are affected by the reforestation of cultivated areas, mainly the groundwater recharge (Woldesenbet et al, 2017), with the increasing soil water infiltration (Yu et al, 2015), as well as a significant reduction of runoff (Li et al, 2012).…”
Section: Resultsmentioning
confidence: 86%
“…The payment for environmental services tends to benefit the understanding of water and soil conservation activities, increasing the supply of environmental services and their understanding of the value of these services and their contribution to the various sectors of society (Vogl et al, 2016). Based on biophysical processes to demonstrate the economic return of integrated environmental interventions, Vogl et al (2017) demonstrated the good economic return of investments considering multiple hydrological services.…”
Section: Introductionmentioning
confidence: 99%
“…At the regional scale, water resources assessments are needed to explore and implement efficient water‐allocation plans (Kirby, Connor, Ahmad, Gao, & Mainuddin, ). For example, the development of hydropower production facilities in Africa or South‐East Asia requires the prediction of annual and monthly flows (Vogl et al, ). In Latin America, the development of investment in watershed services programs requires stakeholders to estimate the effect of land management on hydrological services (Bremer et al, ; Guswa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Erosion control is an important ecosystem service for the hydropower sector, since higher sediment concentrations in streams decrease electricity production (Goldstein et al, 2017;Vogl et al, 2016). As priority areas for the reduction in sediment export, those parts of sub-watersheds that flow to the water catchment points of the Costa Rican hydroelectricity plants are included in the spatial analysis (Figure 33a).…”
Section: Hydropower Productionmentioning
confidence: 99%